2016
DOI: 10.3759/tropics.ms15-13
|View full text |Cite
|
Sign up to set email alerts
|

Soil nutrients and size-dependent tree dynamics of tropical lowland forests on volcanic and sedimentary substrates in Sabah, Malaysian Borneo

Abstract: Soil nutrient concentrations and tree dynamics were examined in two Bornean tropical forests on contrasting geological substrates, one on volcanic and the other on sedimentary rocks. Concentrations of P extracted by the Hadley fractionation method and inorganic N of topsoils were much greater in the volcanic site than in the sedimentary site. Dipterocarps showed greater relative growth rates in the volcanic site than in the sedimentary site at the smallest size class (10 cm ≤ diameter at breast height<20 cm), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…supposed to have low wood density) was positively linked with total P and N but also Mg and Ca. In Sabah, (Aoyagi et al, 2016) found that total P and N acted significantly only on the growth of small trees belonging to the Dipterocapaceae species (but with no information on their wood density).…”
Section: Discussionmentioning
confidence: 99%
“…supposed to have low wood density) was positively linked with total P and N but also Mg and Ca. In Sabah, (Aoyagi et al, 2016) found that total P and N acted significantly only on the growth of small trees belonging to the Dipterocapaceae species (but with no information on their wood density).…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear how mortality rates of tropical tree species vary with fertility, because variation in speciesspecific mortality in relation to soil P gradients has been studied mainly in seedling experiments with a small number of species [13,25,28], while there are many studies examining the relationship between edaphic gradients and stand-level mortality (see below). The growth-mortality trade-off hypothesis predicts that the faster growth rates observed for species adapted to low-P soils in Panama [18,19] should coincide with a higher mortality rate, yet stand-level and seedling mortality rates generally decrease as soil fertility declines across tropical regions [15,[28][29][30][31] (but see [13] for the opposite trend in seedling mortality). A lower mortality rate in infertile environments might be due to greater resource allocation to defence and the reduced effects of natural enemies in species growing in infertile environments [32].…”
Section: Introductionmentioning
confidence: 99%
“…Reserve and secondary forests in the Tangkulap Forest Reserve (Imai et al, 2012). The vegetation and soil characteristics at the sites were reported by Aoyagi et al (2016) and Imai et al (2010). Dipterocarp species constituted 47.5% of the relative basal area (RBA) in the primary forest plot.…”
mentioning
confidence: 99%